Challenges of upgrading craft workforce into Construction 4.0: framework and agreements. Issue 3 (30th June 2020) - Calvetti, Diego; Magalhães, Pedro Nuno Mêda; Sujan, Sujesh Francis; Gonçalves, Miguel Chichorro; Campos de Sousa, Hipólito José
Abstract : Craft workforce is the main productive factor in traditional construction. Construction 4.0 visions are based on automation and digitalisation, meaning that human site activities will require/stipulate changes. The extent to which manual tasks done by humans in construction will be replaced is uncertain. This might vary considering the context or type of work. Construction 4.0 includes craft workforce activities, as these can benefit from technology, fostering digital transformation in the short/medium term. The research scope is workforce–innovation–management using data from job sites. A framework is developed based on data future use involving electronic performance monitoring, building information modelling, smart contracts and artificial intelligence. A systematic scoping review is developed to identify legal/ethical issues in connection to technological aspects. The discussion and findings focus on General Data Protection Regulation compliance to apply the proposed framework. Optimised human–machine-controlled environments must be ethically managed by pre-established collective agreements and must rely on each worker's awareness and consent. The findings suggest that the human aspects if improperly addressed could result in a bottleneck of digital transformation advances. Along with the framework, the paper provides a step-by-step, streamlined review of the regulations and requirements that need to be considered when implementing electronic monitoring of workers.